Profiles of Depressive Symptoms Among Men Who Have Sex With Men and Transgender Women During the COVID-19 Outbreak in Mexico: A Latent Class Analysis - Cerecero-Garcia, Diego; Vermandere, Heleen; Bojorquez, Ietza; Gómez-Castro, José; Arturo Sánchez-Ochoa, José; Martínez-Dávalos, Araczy; Huerta-Icelo, Ivonne; Bautista-Arredondo, Sergio (Frontiers in Public Health, 2021)
The impact of the COVID-19 outbreak on mental health among HIV high-risk populations is not known. We assess the prevalence of depressive symptoms (DS) and explore the association with characteristics related to the COVID-19 pandemic. We conducted an online survey among 881 men who have sex with men (MSM) and transgender women (TGW) assessing the presence of DS using the Center for Epidemiological Studies Depression Scale (CESD-10); results were compared with previously self-reported DS and national data. We applied latent class analysis (LCA) to identify classes of participants with similar COVID-19 related characteristics. The overall prevalence of significant DS was 53.3%. By LCA posterior probabilities we identified three classes: (1) minimal impact of COVID-19 (54.1%), (2) objective risk for COVID-19 (41.5%), and (3) anxiety and economic stress caused by COVID-19 (4.4%). Multivariate logistic regression showed that compared with those in class one, the odds to have significant DS were almost five times higher for those in class three. Our findings suggest high levels of depression among MSM and TGW in Mexico during the COVID-19 pandemic and highlight the need for the provision of targeted psychological interventions to minimize the impacts of COVID-19 on the mental health.